The roles of sodium-glucose cotransporter 2 inhibitors in preventing kidney injury in diabetes - Jaikumkao K. (2017)
© 2017 Elsevier Masson SAS Diabetic nephropathy (DN) is the leading cause of end stage renal disease (ESRD) worldwide. The early effective treatment of high plasma glucose could delay or prevent the onset of DN. Sodium-glucose cotransporter 2 (SGLT2) inhibitors are new target treatments for ameliorating high plasma glucose and help to maintain glucose homeostasis in diabetic patients. Reduced renal glucose reabsorption by SGLT2 inhibition seems to have high potential to improve glycemic control in diabetes mellitus (DM) not only through glucose lowering but also through glucose-independent effects such as blood pressure-lowering and direct renal effects in diabetes. Of note, the important events in the pathogenesis of glucose-induced renal injury and DN including oxidative stress, inflammation, fibrosis and apoptosis conditions have shown to be ameliorate after the treatment with SGLT2 inhibitors. Interestingly, SGLT2 inhibitors have been reported to reduce albuminuria in DM via an activation of renal tubuloglomerular feedback by increased macula densa sodium and chloride delivery, leading to afferent vasoconstriction and attenuated diabetes-induced renal hyperfiltration. These effects also help to conserve glomerular integrity. Thus, the treatment of diabetes mellitus using SGLT2 inhibitors could be one of the effective approach for the management of diabetic-associated kidney disease like DN. This review summarizes the up to date information and discusses the bidirectional relationship between the SGLT2 inhibitor treatments and the renal functions that are available from both basic research and clinical reports. The details of renal outcomes of SGLT2 inhibitors in DN are also provide in this review.